Development of bottled macapuno strings in langka syrup - Soriano, Melissa Aquino; Villarino, Blanca J. (Quezon City University of the Philippines Diliman, 2007)
ABSTRACT This study aimed to develop bottled macapuno strings in langka syrup. Three langka syrup concentrations (10%, 20%, 30%) were prepared to determine the most acceptable formulation to be added to macapuno strings. Moreover, the thermal process schedule for the bottled macapuno strings in the most acceptable langka syrup was established using Ball's mathematical method. Verification of the calculated process was likewise conducted. Ten percent langka syrup was determined to have no significant difference (p > 0.05) with the other two formulations in terms of over-all accpetance and , thus, was used in establishing the process of bottled macapuno strings for economic reasons. Using Clostridium pasteurianum as the reference organism, the calculated process was approximately 51 minutes. This was further verified through the favorable cut-out tests, physico-chemical test, microbial analysis and sensory evaluation. Results showed that the process used for the product is adequate to produce a safe and acceptable bottled macapuno strings in langka syrup.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fruit preservation; Macapuno